ACADEMIC INTEGRITY AS A DETERMINANT OF HIGHER EDUCATION QUALITY ASSURANCE - Liuta, Olha; Deineka, Olha; Artyukhova, Nadiia; Hrytsenko, Larysa; Daher Kаtheryna (Socio-economic relations in the digital society, 2025)
The aim of this article is to define the role of academic integrity as a key factor in ensuring the quality of higher education, to analyse the existing problems in this area and to develop recommendations for improving the level of integrity in the educational process. The article analyses the principles of academic integrity and its impact on the quality of educational processes. It was found that effective implementation of the integrity policy helps to reduce the level of academic misconduct, increase trust in educational institutions and improve the reputation of universities. The main mechanisms for ensuring academic integrity are considered, including regulatory control, digital technologies for checking plagiarism, educational programmes on academic writing and the creation of ethics commissions. Academic integrity is an essential component of high-quality education that ensures responsibility, transparency and fairness in the learning process. Prevention of plagiarism, falsification and other violations is possible only with a comprehensive approach that includes both preventive measures and responsibility for non-compliance with ethical standards. Further research should be aimed at improving the mechanisms of control and promoting a culture of integrity among students and university teachers.